Resposta da pressão arterial pós-exercício e seus fatores associados - Marques Ferreira, Laryssa (2022)
Introduction: in Academia da Cidade, hypertensive individuals involved in daily exercise practice, but fewer studies have been developed about blood pressure (BP) behavior in these spaces. Another gap refers to the predictive factors for the blood pressure response. Aim: to investigate the blood pressure behavior and to analyze its predictive factors during exercise. Methods: observational study, carried out between December of 2018, January to February 2019. Sixteen hypertensives (58.8 ± 15.3 years) took part in the exercise practice. BP and heart rate were checked before and after each exercise session. Heart rate variability was assessed in April. Statistical analysis was carried out with One-way ANOVA and linear regression. Results: the systolic BP (SBP) at rest did not decrease between the months of observation. The diastolic BP (DBP) at rest decreased between December and January (79.3±9.7mmHg to 73.0±7.1 mmHg, p=0.02, Cohen's D =0.77). In April, for post-training PAS, SDNN (β:1.6, 95%CI: 0.3-0.6, p=0.0), RMSSD (β:-2.0, 95%CI: -2.3 - -1.5, p=0.0) and pre-exercise SBP (β:0.6, 95%CI:0.3-0.8, p=0.0) were predictors. For the post-exercise DBP, the LF/HF (β:-0.9, 95%CI:-4.2 - -0.8, p=0.0) and the pre-exercise DBP (&beta:0, 8, 95%CI: 0.4-1.4, p=0.0) were predictors. Other relations were observed between February and March. Conclusion: only the PAD reduced significantly. Variables of the autonomic nervous system, systolic or diastolic pre-exercise blood pressure and heart rate during exercise practice predicted the behavior of post-exercise blood pressure.